2002
DOI: 10.1089/107632702320934010
|View full text |Cite
|
Sign up to set email alerts
|

Bone Tissue-Engineered Implants Using Human Bone Marrow Stromal Cells: Effect of Culture Conditions and Donor Age

Abstract: At present, it is well known that populations of human bone marrow stromal cells (HBMSCs) can differentiate into osteoblasts and produce bone. However, the amount of cells with osteogenic potential that is ultimately obtained will still be dependent on both patient physiological status and culture system. In addition, to use a cell therapy approach in orthopedics, large cell numbers will be required and, as a result, knowledge of the factors affecting the growth kinetics of these cells is needed. In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
117
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(133 citation statements)
references
References 27 publications
(33 reference statements)
12
117
2
Order By: Relevance
“…A negative correlation between donor age, number and proliferative capacity of MSCs isolated from young and old donors has been demonstrated by several authors (Martin et al 1970, Schneider & Mitsui 1976, Majors et al 1997, D'Ippolito et al 1999, Stenderup et al 2003, Mareschi et al 2006, but widely different results have been obtained with regard to MSC antigen expression. Recently, Stolzing et al (2008) confirmed those already demonstrated in previous studies (D 'Ippolito et al 1999, Mendes et al 2002, Chen et al 2005, Zhang et al 2005, Zheng et al 2007, Kretlow et al 2008, observing a significant age-related change in membrane markers expression levels, an alkaline phosphatase activity, chondrogenic and myogenic differentiation potency decline with donor age in contrast with adipogenic differentiation. However, these data are in contrast with those reported by other research groups (Bergman et al 1996, Stenderup et al 2001, Bellows et al 2003, which showed no age-related differences in differentiation potency.…”
Section: Introductionsupporting
confidence: 85%
“…A negative correlation between donor age, number and proliferative capacity of MSCs isolated from young and old donors has been demonstrated by several authors (Martin et al 1970, Schneider & Mitsui 1976, Majors et al 1997, D'Ippolito et al 1999, Stenderup et al 2003, Mareschi et al 2006, but widely different results have been obtained with regard to MSC antigen expression. Recently, Stolzing et al (2008) confirmed those already demonstrated in previous studies (D 'Ippolito et al 1999, Mendes et al 2002, Chen et al 2005, Zhang et al 2005, Zheng et al 2007, Kretlow et al 2008, observing a significant age-related change in membrane markers expression levels, an alkaline phosphatase activity, chondrogenic and myogenic differentiation potency decline with donor age in contrast with adipogenic differentiation. However, these data are in contrast with those reported by other research groups (Bergman et al 1996, Stenderup et al 2001, Bellows et al 2003, which showed no age-related differences in differentiation potency.…”
Section: Introductionsupporting
confidence: 85%
“…However, the use of hBMSCs has limitations. First, the self-renewal and proliferative ability of hBMSCs decreases due to aging [17][18][19] and diseases, such as osteoporosis and arthritis. 20,21 Second, the heterogeneity of adult stem cells from bone marrow indicates that only a very small proportion of cells can be considered stem cells and can differentiate into the osteogenic lineage.…”
mentioning
confidence: 99%
“…Three different cases were considered: young (up to 20 years old), adult (about 55 years old) and elder (more than 70 years old) patients. Based on the histological analyses conducted by Chen et al, (Chen et al, 2005), Baxter et al, (Baxter et al, 2004), Mendes et al (Mendes et al, 2002), and Park et al (Park et al, 2005), the diffusion coefficient D was hypothesized to be a function of the patient's age. Let t elder , t adult and t young be the time periods required by MSCs for recovering completely the bone callus domain respectively for the elder, adult and young patients.…”
Section: Determination Of the Optimal Duration Of The Latency Period mentioning
confidence: 99%